2016
DOI: 10.1182/blood-2014-05-578781
|View full text |Cite
|
Sign up to set email alerts
|

Apelin: an antithrombotic factor that inhibits platelet function

Abstract: Key Points• Apelin plays a key role in maintaining hemostasis through the regulation of platelet function.• Treatment of platelets with apelin inhibits aggregation and thrombus formation.Apelin peptide and its receptor APJ are directly implicated in various physiological processes ranging from cardiovascular homeostasis to immune signaling. Here, we show that apelin is a key player in hemostasis with an ability to inhibit thrombin-and collagenmediated platelet activation. Mice lacking apelin displayed a shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
52
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 50 publications
(67 reference statements)
4
52
0
2
Order By: Relevance
“…In the cardiovascular system, apelin/APJ system can reduce blood pressure, promote the formation of new blood vessels, reduce arterial tension, and the heart preload (Yu et al, ). In addition, apelin/APJ system can regulate gastrointestinal function and insulin sensitivity, promote cell proliferation and migration, induce angiogenesis, and regulate immune function (Adam et al, ; Castan‐Laurell et al, ; Lv et al, ; Tiani et al, ; Wang et al, ; Zhou, Cao, & Chen, ). Various researches show that apelin may play a role in body fluid homeostasis (Najafipour, Soltani Hekmat, Nekooian, & Esmaeili‐Mahani, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the cardiovascular system, apelin/APJ system can reduce blood pressure, promote the formation of new blood vessels, reduce arterial tension, and the heart preload (Yu et al, ). In addition, apelin/APJ system can regulate gastrointestinal function and insulin sensitivity, promote cell proliferation and migration, induce angiogenesis, and regulate immune function (Adam et al, ; Castan‐Laurell et al, ; Lv et al, ; Tiani et al, ; Wang et al, ; Zhou, Cao, & Chen, ). Various researches show that apelin may play a role in body fluid homeostasis (Najafipour, Soltani Hekmat, Nekooian, & Esmaeili‐Mahani, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the cardiovascular system, apelin/ APJ can strengthen cardiac contractility, relax blood vessels and lower blood pressure (10,11). In addition, apelin/APJ can regulate gastrointestinal function and insulin sensitivity, and can promote cell proliferation, migration and angiogenesis, thus regulating immune function (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…Adam et al [4] recently reported that apelin/APJ receptor is expressed in human and mouse platelets. Apelin-13 inhibits a low concentration of thrombin-or collagen-induced platelet aggregation in human and mouse.…”
mentioning
confidence: 99%
“…These data indicated that apelin-13 is directly involved in the regulation of platelet activation. Furthermore, Adam et al [4] also explored the antiplatelet mechanism of apelin-13 in detail. First, platelets stimulated with agonists were found to result in transient activation of integrins.…”
mentioning
confidence: 99%
See 1 more Smart Citation